Social support and psychological well-being among older Malay women in Peninsular Malaysia - Yahaya, Nurizan; Momtaz, Yadollah Abolfathi; Tengku Abdul Hamid, Tengku Aizan; Abdullah, Siti Suhailah (Indian Gerontological Association, 2013)
Research shows older women are at increased risk for poor psychological well-being. The present study investigated the effects of social support on psychological well-being of a random sample of 716 older Malay women which obtained from a national survey. Findings from multiple regression analysis revealed a significant model (F=15.06, p≤.05) where psychological well-being was best predicted by non-family support (ß=.22, p≤.001) and family support (ß =.10, P≤.01), after controlling for sociodemographic factors. Results of this study imply that social support especially from non-family source is a significant predictor of psychological well-being among older women.